Novel functionalized synthetic rubbers for tyre applications - Thiel KHSven; Kiesekamp Joachim; Ruehmer Thomas; Schkopau (Kautschuk Gummi Kunststoffe, 2013)
Functionalized synthetic rubbers need to be selected for the production of low rolling resistance tires also having well balanced wet skid & abrasion resistance properties. The synthetic rubber business of styron operating in the area of synthetic rubber, particularly SSBR, SBR high and low cis-polybutadiene, is constantly extending the production volume and the scope of functionalized polymer grades. In October 2012 a new SSBR manufacturing plant with an annual capacity of 50.000 MT was going on stream. Furthermore, a tailor made functionalized neodymium catalyst made HCBR/modified SSBR polymer set was developmed.
Keywords: Functionalizeed rubber; HCBR; high cis-polybutadiene; Modified polymers; Modified rubber; Polybutadiene; Rolling resistance; Rubber formulations; Solution Styrene-Butadiene rubber; SSBR; Styrene-Butadiene Copolymers; Synthetic rubber; Synthetic Rubber